Implementasi Chat Room dan Push Notification pada e-Class Berbasis Mobile - Vievin Efendy; Kristian Adi Nugraha; Danny Sebastian (Jurnal Teknik Informatika dan Sistem Informasi, 2019)
e-Class is one of the applications of e-Learning that has been applied at Duta Wacana Christian University as an educational facilities. The utilization of e-Class has help both lecturers and students to share lecture material and other supporting academic data. However, e-Class does not yet support notification for latest information and real time discussion columns. In answering the problems faced by e-Class site users, the development of mobile-based e-Class applications that are integrated with e-Class sites can be one of solution. The e-Class application provides the same features as e-Class sites and with the use of Firebase Cloud Messaging technology helps answer the latest notifications issues and the Firebase Realtime Database to create chat rooms in real time. The application that was built was tested using task scenario and UEQ as parameters for the level of efficiency, effectiveness and convenience in the use of the application. The results obtained by the application are fairly good to implement and the results of the UEQ scale average are worth excellence. Further research that is expected from this research is to increase the efficiency of the mobile-based e-Class application.